The Interdisciplinary Stem Cell Institute’s Use of Food and Drug Administration-Expanded Access Guidelines to Provide Experimental Cell Therapy to Patients With Rare Serious Diseases - Khan, Aisha; Bellio, Michael A.; Schulman, Ivonne H.; Levi, Allan D.; Longsomboon, Bangon; Brooks, Adriana; Valasaki, Krystalenia; DiFede, Darcy L.; Pujol, Marietsy V.; Yavagal, Dileep R.; Bates, Karen E.; Si, Ming-Sing; et al. (Frontiers in Cell and Developmental Biology, 2021)
The U.S. Food and Drug Administration (FDA) provides guidance for expanded access to experimental therapies, which in turn plays an important role in the Twenty-first Century Cures Act mandate to advance cell-based therapy. In cases of incurable diseases where there is a lack of alternative treatment options, many patients seek access to cell-based therapies for the possibility of treatment responses demonstrated in clinical trials. Here, we describe the use of the FDA’s expanded access to investigational new drug (IND) to address rare and emergency conditions that include stiff-person syndrome, spinal cord injury, traumatic brain stem injury, complex congenital heart disease, ischemic stroke, and peripheral nerve injury. We have administered both allogeneic bone marrow-derived mesenchymal stem cell (MSC) and autologous Schwann cell (SC) therapy to patients upon emergency request using Single Patient Expanded Access (SPEA) INDs approved by the FDA. In this report, we present our experience with 10 completed SPEA protocols.